Zakat as a Solution for Budget Deficits and Foreign Debt - Gumilar, Dedi (Journal of Economicate Studies, 2021)
This article discusses the potential of zakat as a source of state revenue and proposals for its management. Three problems come together in 2021, namely the problem of state and BUMN finances due to poor management of the State Budget and BUMN finances. The state budget deficit has widened so that it is impossible for the government to cover it with new debt. In the view of sharia, zakat is a major component in state finances, the Prophet Muhammad had appointed Muadz bin Jabal to be the emir and collector of zakat in Yemen. Abu Bakr also continued the guidance of the Prophet Muhammad. After the death of the Prophet Muhammad, Abu Bakr fought those who did not want to give zakat. The study was conducted with a qualitative analysis of data sources obtained from secondary data, namely, data from the Ministry of Finance of the Republic of Indonesia, Bank Indonesia, the Central Bureau of Statistics (BPS), and the National Zakat Agency (BAZNAS). The technique of collecting data is by quoting data published by each institution on the website. The crucial problem is the low awareness of the Muslim community of paying zakat, because the existing regulations categorize zakat as voluntary acceptance, there are no rules that have legal consequences for Muslim communities who do not pay zakat. The conclusion of this research is that the low income of zakat compared to its potential requires serious attention from the government by issuing new regulations, so that zakat will make a major contribution to state revenue as well as taxes.